Grip and Pinch Strengths in Young Adults Residing in Tehran (2017): Development of Prediction Models - Sajjad Rostamzadeh; Mahnaz Saremi; Hashem Vahabzadeh-Monshi; Parvin Yazdanparast (Iranian Journal of Health, Safety and Environment, 2020)
Hand strength is necessary for many daily, working and leisure activities. The aim of this study was to determine the predictors of handgrip and pinch strengths among Iranian young adults. A cross-sectional study was designed in which 716 young adults (354 males, 24.1 years ± 3.2; 362 females, 23.1 years ± 3.6) participated. Demographic characteristics, as well as the length of the hand, palm and forearm, the palm width, and the circumference of wrist and forearm, were measured. A tape meter (± 0.1cm), and a digital Caliper (± 0.1 mm) were used to measure anthropometric dimensions. Jamar hydraulic dynamometer and pinch gauge were used to measure Hand Grip Strength (HGS) as well as Tip (TP), Key (KP) and Palmar (PP) pinch strengths. Mean values of HGS, TP, KP and PP varied from 25.6 to 80, 4.1 to 8.7, 6.4 to 14.7 and 5.4 to 12.7Kg in men and from 14 to 39, 3.2 to 6.0, 4.7 to 8.1 and 3.4 to 9.3Kg in women, respectively. Multiple linear regression analysis showed gender, age, height and BMI as the best predictors of hand strengths. The values of hand strengths are easily predictable using a few readily available individual attributes. Results may serve as a benchmark for job selection.